Effect of temperature on the optical and morphological properties of zinc oxide thin films prepared by RF magnetron sputtering - Mohamad, Souad A.; Othman, Maizatulnisa (2014)
This investigation deals with the effect of temperature on the optical and morphological properties of Zinc Oxide thin films prepared by radio-Frequency (RF) magnetron sputtering technique. In the present work, zinc oxide (ZnO) thin films have been deposited on glass substrates from 50°C to 300°C by radio frequency magnetron sputtering. The effects of deposition temperature on the crystallization behaviour and optical properties of the films have been studied. The thin films were characterized using Ultraviolet Visible Spectroscopy (UV-VIS), Field Emission Scanning Electron Microscopy (FESEM) and X-ray Diffraction Analysis (XRD). From the UV-VIS testing, the average transmission percentage of the films is between 80-95% for all deposition temperatures meanwhile the energy gap of ZnO thin films varies from 3.26 eV to 3.35 eV which is not much different from the theoretical value. Also, the grain size is getting smaller from 3.886nm, 3.216nm, 3.119nm and 3.079nm with respect to the increasing deposition temperature 50°C, 100°C, 200°C and 300°C respectively whereas the average grain size per intercept value is increasing. The patterns of the peak were about the same for all deposition temperature where the thin films have polycrystalline hexagonal wurtzite structure with the orientation perpendicular (002) to the substrate surface (c-axis orientation) at 34.5(2).